Residential interior design a guide to planning spaces - Mitton, Maureen (Wiley, 2006)
"More than a decorating guide, Residential Interior Design teaches the fundamental skills needed to plan interior spaces for all types of homes, in all decorative styles, from remodeling to new construction. Taking a step-by-step approach, this primer reviews all aspects of interior architecture as it relates to human factors and daily use." "Authors and interior designers Maureen Mitton and Courtney Nystuen explore the minimal amount of space necessary in order to rooms to function usefully, from the kitchen to the bathroom, the bedroom to the hallway, and every room in between. Packed with hundreds of drawings and photographs, this valuable tool is brimming with useful information regarding codes, mechanical and electrical systems, the Americans with Disabilities Act, accessibility codes, special considerations for multi-family dwellings, and a variety of additional factors that impact each type of room and its corresponding space."--Jacket.